LEGAL PROTECTION OF SUBSCRIPTION BROADCASTING INSTITUTIONS AGAINST ILLEGAL SUBSCRIPTION BROADCASTING BASED ON LAW NO 32 OF 2002 CONCERNING BROADCASTING - Raden Handiriono (JILPR Journal Indonesia Law and Policy Review, 2023)
Broadcasting activities in Indonesia are divided into various kinds, namely broadcasts by public broadcasters and subscription broadcasters. Subscription Broadcasting is a broadcasting operator of a commercial nature in the form of an Indonesian legal entity, whose business field is only to provide subscription broadcasting services. The purpose of this research is to find out the concept of legal protection of subscription broadcasting institutions against broadcasting carried out by broadcasting providers carried out by subscription broadcasters based on Law No. 32 of 2002. The method used is normative juridical. The specification of the research used is descriptive analytical which provides an overview of the protection of subscribed broadcasting institutions, according to Law number 32 of 2002 concerning broadcasting. The analysis techniques used are descriptive techniques, interpretive techniques, evaluative techniques, systematic techniques, and argumentative techniques. Data collection is carried out through library research, either directly or virtually by studying data from laws and regulations related to the problem. The results of the study conclude that the concept of legal protection of subscription broadcasting institutions as stated in the provisions of the law is a broadcasting institution in the form of an Indonesian legal entity, whose line of business is only to provide subscription broadcasting services and must first obtain a subscription broadcasting license with the aim of assisting the public in obtaining protection. the law of broadcasting institutions against broadcasting carried out by subscription broadcasters based on Law NO. 32 of 2002.